(untitled) (Simbiótica. Revista Eletrônica, 2023)
The morphogenetic approach of sociologist Margaret Archer, beyond the issue of reflexivity, is little diffused in Brazil, despite the existence of some introductory works about Critical Realism in the country. Such perspective, eminently philosophical, emphasizes the ontological dimension when it comes to the investigation of social reality, which certainly reverberated in the author’s thought. For this reason, this article seeks to detail the theoretical logic proposed by the author about the relationship between agency, structure, and culture over time. The article is structured in the following way: (1) it begins by briefly presenting Margaret Archer’s intellectual trajectory and the main aspects of her morphogenetic approach; (2) it exposes the ontological and epistemological bases on which the author used to do so; (3) it details the application of the morphogenetic approach; and, finally (4) it exposes the main criticisms to its operationalization, based on ontological, epistemological and space-temporal arguments from secondary literature.